2021
DOI: 10.2147/idr.s291867
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of microRNA-340-5p Ameliorates Inflammatory Response and Intracellular Survival of Mycobacterium Tuberculosis in Alveolar Type II Cells

Abstract: Background:The importance of microRNAs (miRs) has been documented in infections. This study estimated the role of miR-340-5p in Mycobacterium tuberculosis (Mtb)-infected alveolar type II cells. Methods: The microarray of GEO database was analyzed to find the differentially expressed miRs caused by Mtb infection, and miR-340-5p was selected as the research object. The effects of Mtb infection on A549 cells were studied by MTT, CFU, EdU, flow cytometry and ELISA assays. miR-340-5p expression was altered in Mtb-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Notably, TMED7 has been reported to be a cis-related gene of NF-κB [ 54 ]. Studies in alveolar type-II cells have shown that microRNA-340-5p has anti-inflammatory effects by inhibiting TMED7 and thus the activation of NF-κB [ 55 ]. Whether LPC 16:0 also modulates the TMED7/NF-κB axis in human FLSs remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, TMED7 has been reported to be a cis-related gene of NF-κB [ 54 ]. Studies in alveolar type-II cells have shown that microRNA-340-5p has anti-inflammatory effects by inhibiting TMED7 and thus the activation of NF-κB [ 55 ]. Whether LPC 16:0 also modulates the TMED7/NF-κB axis in human FLSs remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Severe inflammatory disorders like sepsis can develop as a result of abnormal TLR4 signaling 36 . Another study shown that miR-340-5p overexpression reduced the harm that Mycobacterium TB infection caused to A549 cells by activating the TMED7/NF-B axis 88 . After lipopolysaccharide (LPS) stimulation of human monocytes, TMED7 exhibits a biphasic rise.…”
Section: Tmed Genes In Immune Responsementioning
confidence: 99%